2018
DOI: 10.3389/fpls.2018.01224
|View full text |Cite
|
Sign up to set email alerts
|

Canola Responses to Drought, Heat, and Combined Stress: Shared and Specific Effects on Carbon Assimilation, Seed Yield, and Oil Composition

Abstract: Photosynthetic assimilation is remarkably altered by heat and drought, and this depends on the individual or combined occurrence of stressors and their respective intensities and durations. Abiotic stressors may also alter the nutritional quality and economic value of crops. In this controlled greenhouse study, we evaluated the response of Brassica napus L., from flowering to seed development, to two temperature and water treatments and a combination of these treatments. The diffusional limitations of stomatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 105 publications
5
82
0
1
Order By: Relevance
“…However, Elferjani and Soolanayakanahally (2018) found an opposite response. Using 10 years of field data and following a modelling approach, Baux et al (2013) observed an increase in oleic acid (C18:1) in conventional oilseed rape and high-oleic low-linolenic (HOLL) varieties associated with minimum temperature, coincided by a decrease in linoleic acid (C18:2) and linolenic acids (C18:3) concentration.…”
Section: Hnt Alters Saturated Fatty Acids But Not Unsaturated Fattymentioning
confidence: 87%
See 2 more Smart Citations
“…However, Elferjani and Soolanayakanahally (2018) found an opposite response. Using 10 years of field data and following a modelling approach, Baux et al (2013) observed an increase in oleic acid (C18:1) in conventional oilseed rape and high-oleic low-linolenic (HOLL) varieties associated with minimum temperature, coincided by a decrease in linoleic acid (C18:2) and linolenic acids (C18:3) concentration.…”
Section: Hnt Alters Saturated Fatty Acids But Not Unsaturated Fattymentioning
confidence: 87%
“…Previous studies demonstrate that HDT stress during pod filling results in reduced oil concentration and increased protein concentration in oilseed crops (Aksouh-Harradj et al, 2006;Singer, Zou, & Weselake, 2016;Zhu et al, 2012 [canola]), (Dombos & Mullen, 1992;Gibson & Mullen, 1996 [soybean]). Similarly, a negative correlation between monounsaturated and polyunsaturated fatty acids has been observed with HDT stress exposure in a number of oilseed crops, including canola (Aksouh-Harradj et al, 2006;Baux et al, 2013;Deng & Scarth, 1998;Elferjani & Soolanayakanahally, 2018), sunflower (Nagao & Yamazaki, 1984;Flagella, Rotunno, Tarantino, Di Caterina, & De Caro, 2002) and soybean (Dornbos & Mullen, 1992;Gibson & Mullen, 1996). In summary, day-time heat stress is shown to alter the oil and protein composition and reduce beneficial monoand polyunsaturated fatty acids, while the impact of HNT on these fatty acids is not known either in canola or in other Brassica species.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Different abiotic stresses adversely affect major biological processes in plants such as photosynthesis, stomatal conduction, rate of transpiration, protein synthesis, and metabolite accumulation (Zhang X. et al, 2014;Zhu et al, 2016;Elferjani and Soolanayakanahally, 2018). Abiotic stresses and their physiological consequences on plants are both shared and unique (Chinnusamy et al, 2004).…”
Section: Physiological Impact Of Abiotic Stress In Canolamentioning
confidence: 99%
“…Grown in the temperate climates of both northern and southern hemispheres, it is cultivated in different seasons (annuals or biennials) (Shahzadi et al, 2015;Zhu et al, 2016). Just like other temperate field crops, B. napus is also susceptible to multiple abiotic stresses (Elferjani and Soolanayakanahally, 2018). Drought, salinity, extreme temperatures, and cadmium toxicity are the most prevalent abiotic stresses affecting the growth and development of B. napus.…”
Section: Introductionmentioning
confidence: 99%